Role of Endolysosomes in Skeletal Muscle Pathology Observed in a Cholesterol-Fed Rabbit Model of Alzheimer’s Disease - Chen, Xuesong; Wagener, John F.; Ghribi, Othman; Geiger, Jonathan D. (Frontiers in Aging Neuroscience, 2016)
Deficits in skeletal muscles contribute not only to the functional decline in people living with Alzheimer’s disease (AD), but also to AD pathogenesis. We have shown that endolysosome dysfunction plays an important role in the development of AD pathological features in a cholesterol-fed rabbit model of AD. Interestingly we observed in skeletal muscle from the rabbit AD model increased deposition of Aβ, phosphorylated tau, and ubiquitin. Here, we tested the hypothesis that endolysosome dysfunction commonly occurs in skeletal muscle and brain in this rabbit model of AD. In skeletal muscle of rabbits fed a 2% cholesterol-enriched diet for 12 weeks we observed the presence of abnormally enlarged endolysosomes, in which were increased accumulations of free cholesterol and multiple AD marker proteins subject to misfolding and aggregation including Aβ, phosphorylated tau, and ubiquitin. Moreover, in skeletal muscle of rabbits fed the cholesterol-enriched diet we observed decreased specific activities of three different lysosome enzymes. Our results suggest that elevated levels of plasma cholesterol can disturb endolysosome structure and function as well as promote the development of AD-like pathological features in skeletal muscle and that these organellar changes might contribute to the development of skeletal muscle deficits in AD.